1973
DOI: 10.1073/pnas.70.1.98
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Mitochondrial Adenosine Diphosphate Uptake by Thyroid Hormones

Abstract: Thyroid hormone administered in vivo increased carrier-mediated (atractyloside-sensitive) ADP uptake by rat liver mitochondria. 3 Days after a single large dose of triiodothyronine (20 ;g/100 g of body weight), mitochondrial uptake of ADP measured at 60 was 2.35 4 0.17 nmol/min per mg of protein, compared with an uptake of 1.81 i 0.19 nmol/min per mg of protein in mitochondria from untreated rats (P < 0.025). Cyanide (1.33 mM) had no effect on ADP uptake by mitochondria from either untreated or triiodothyronin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

1979
1979
2012
2012

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(24 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…We showed that thyroid deficiency led to an increase in the apparent Km of the ANT of rat liver mitochondria from the euthyroid value of 2.8 ~M to 6.3 p.M and that this was returned to normal 15 rain after a near-physiological intravenous dose of T3 [5]. Increases in the ANT transport rate at longer times after thyroid hormone administration reported by others [25,26] probably reflect an increased number of transporters in the membranes. The data shown in Table 1 demonstrate that, in agreement with these earlier findings, the highly significant decrease in the transport rate in hypothyroid preparations observed at a concentration of ADP near to the Km is not detectable at a much higher concentration.…”
Section: The Effect Of Thyroid Hormone and Ca 2+ Ions On The Rate Of mentioning
confidence: 69%
“…We showed that thyroid deficiency led to an increase in the apparent Km of the ANT of rat liver mitochondria from the euthyroid value of 2.8 ~M to 6.3 p.M and that this was returned to normal 15 rain after a near-physiological intravenous dose of T3 [5]. Increases in the ANT transport rate at longer times after thyroid hormone administration reported by others [25,26] probably reflect an increased number of transporters in the membranes. The data shown in Table 1 demonstrate that, in agreement with these earlier findings, the highly significant decrease in the transport rate in hypothyroid preparations observed at a concentration of ADP near to the Km is not detectable at a much higher concentration.…”
Section: The Effect Of Thyroid Hormone and Ca 2+ Ions On The Rate Of mentioning
confidence: 69%
“…It has been observed that the ATP\ADP exchange is enhanced in liver mitochondria isolated from hyperthyroid rats and diminished in the hypothyroid state [5]. However, there are conflicting data as to whether this alteration in ADP\ATP exchange is due to corresponding alterations in gene expression.…”
Section: Introductionmentioning
confidence: 90%
“…the FAD-linked glycerol 3-phosphate dehydrogenase (mGPDH) are targets of thyroid hormone action [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The voluminous data that have resulted strongly suggest that the thyroid hormones exert a primary effect at the level of the cell nucleus (1)(2)(3)(4)(5), and perhaps the mitochondrion as well (6)(7)(8). In addition, evidence has grown that the thyroid hormones may also exert a direct effect that the level of the cell membrane.…”
Section: Introductionmentioning
confidence: 99%